#1**+1 **

\(1)\frac{7}{4n}-\frac{2n+4}{15n-3}=\frac{7}{4n}-\frac{2n+4}{3(5n-1)}\\ 2)\frac{21(5n-1)}{12n(5n-1)}-\frac{8n^2+16n}{12n(5n-1)}\\ 3)\frac{105n-21-16n-8n^2}{12n(5n-1)}\\ 4)\frac{89n-21-8n^2}{12n(5n-1)} \)

further explanations:

step 1 --> i just factored out the 3 from the right expression's denominator to make it easier to work with

step 2 --> trying to get both expressions to have common denominators, i multiply the left expression's numerator and denominator by 3(5n-1); i also multiply the right expression's numberator and denominator by 4n

step 3 --> i subtract the numerator of the left and right expressions since the denominators are now the same

step 4 --> simplify and get **choice #3**

ChowMein Apr 20, 2020